1996
DOI: 10.1056/nejm199610313351804
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glucose Transport–Phosphorylation and Muscle Glycogen Synthesis after Exercise Training in Insulin-Resistant Subjects

Abstract: Exercise increases insulin sensitivity in both normal subjects and the insulin-resistant offspring of diabetic parents because of a twofold increase in insulin-stimulated glycogen synthesis in muscle, due to an increase in insulin-stimulated glucose transport-phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
439
4
12

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(486 citation statements)
references
References 27 publications
31
439
4
12
Order By: Relevance
“…The depletion of the muscle lipid and/or glycogen stores has been associated with exercise-induced increase in skeletal muscle insulin sensitivity [24,[49][50][51]. Consequently, it could be speculated that exercise interventions that augment IMTG and/or glycogen use are more effective in improving insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of the muscle lipid and/or glycogen stores has been associated with exercise-induced increase in skeletal muscle insulin sensitivity [24,[49][50][51]. Consequently, it could be speculated that exercise interventions that augment IMTG and/or glycogen use are more effective in improving insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, insulin resistance is known to improve by approximately 20% after 1 h of aerobic exercise in healthy (35,36), insulin-resistant (37) and diabetic subjects (36,38) -improvements that are equivalent in magnitude to those achieved through chronic pharmacological intervention (39,40). The augmented insulin sensitivity is apparent immediately after exercise (36) and persists for 20 h to 48 h thereafter (35,37,38). It is also well established that a single bout of aerobic exercise results in 10% to 25% reductions in triglycerides (TGs) and 7% to 15% increases in high-density lipoprotein (HDL) cholesterol levels (11,(41)(42)(43).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…Physical activity can reduce muscle insulin resistance [20,21]; however, studies have also shown that physical activity is associated with a lower intrahepatic fat content [22], and that intrahepatic fat content is associated with hepatic insulin sensitivity [23,24]. Consequently, a differential effect of physical activity on progression to diabetes in individuals with i-IFG and i-IGT could be expected.…”
Section: Introductionmentioning
confidence: 99%